Molecular gastronomy: the influence of hedonic characteristics and perceived values on chefs’ acceptance towards Asam Pedas / Farhan Faat - Faat, Farhan (2014)
The latest development in culinary realm has made chefs all over the world to improvise the traditional food into a different perspectives in developing new food. It successfully evoke the diners emotional experience through surprise elements. This emerging knowledge which combines science and cooking in the preparation of dishes is known as molecular gastronomy. However, in developing countries the understanding of this term and acceptance is still in the introductory stage, as the study to seek knowledge and deeper understanding of molecular gastronomy movement in Malaysia is new. The incorporation of molecular gastronomy knowledge in Malay cuisines could increase the value of ethnic food, provide a new perspective and perception of how traditional food can be at par with molecular western cuisines. This exploratory research empirically investigates the hedonic characteristics and perceived values of Malay cuisine as molecular gastronomy product (asarn pedas) on chefs' acceptance. Through a series of descriptive and inferential statistic. The findings of this study revealed that product hedonic characteristics {fi = .924, p < 0.05) and perceived values (ft = .930, p < 0.05) have a significant influence on chefs' acceptance of molecular gastronomy product (asam pedas). Keyword : Hedonic Characteristic, Perceived Values, Chefs' Acceptance, Malaysia, Malay Cuisine, Asam Pedas, Molecular gastronomy, Molecular cuisine.